Pengaruh Latihan Inch Worm terhadap Kelenturan Otot Punggung Pada Atlet Sepakbola - Oca Fernandes AF; Faujiah Br Barus; Meri Haryani; Tofikin Tofikin (Departement of Mathematics Education, 2023)
The case in this study, that flexibility in soccer players is still not optimal. Due to the lack of movement in the back muscles of the players. The aim of this research is to see the effect of the Inch worm exercise on the flexibility of soccer players. This type of research is a quasi-experimental to see the effect of the form of training. The population in the study were all junior SSB Pekanbaru soccer athletes, totaling 17 people. The method of taking illustrations is by total sampling, which means that all populations used as illustrations so that the illustrations in this study totaled 17 people. The instrument in this research uses the Sit and Reach test to see flexibility. The analysis was attempted using the t-test. Based on the analysis of data and reviews, it can be concluded that there is an effect of inch worm training on flexibility in soccer players tested with a tcount of 6,738 ttable1. 748 at α = 0.05. This ensures that by doing the inch worm exercise, flexibility gets better results so that athletes can easily understand how to play soccer by producing good flexibility.